Associations between neighborhood socioeconomic status, parental education, and executive system activation in youth. (28th March 2022) - Murtha, Kristin; Larsen, Bart; Pines, Adam; Parkes, Linden; Moore, Tyler M; Adebimpe, Azeez; Bertolero, Maxwell; Alexander-Bloch, Aaron; Calkins, Monica E; Davila, Diego G; Lindquist, Martin A; Mackey, Allyson P; et al.
Abstract: Socioeconomic status (SES) can impact cognitive performance, including working memory (WM). As executive systems that support WM undergo functional neurodevelopment during adolescence, environmental stressors at both individual and community levels may influence cognitive outcomes. Here, we sought to examine how SES at the neighborhood and family level impacts task-related activation of the executive system during adolescence and determine whether this effect mediates the relationship between SES and WM performance. To address these questions, we studied 1, 150 youths (age 8–23) that completed a fractal n -back WM task during functional magnetic resonance imaging at 3T as part of the Philadelphia Neurodevelopmental Cohort. We found that both higher neighborhood SES and parental education were associated with greater activation of the executive system to WM load, including the bilateral dorsolateral prefrontal cortex, posterior parietal cortex, and precuneus. The association of neighborhood SES remained significant when controlling for task performance, or related factors like exposure to traumatic events. Furthermore, high-dimensional multivariate mediation analysis identified distinct patterns of brain activity within the executive system that significantly mediated the relationship between measures of SES and task performance. These findings underscore the importance of multilevel environmental factors in shaping executive system function and WM in youth.